NEUROLOGY APPLIED TO HEALTH EDUCATION (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2026)
Stroke is a leading cause of morbidity and mortality worldwide, associated with high rates of disability and death, and in most cases linked to cardiovascular factors. Systemic arterial hypertension (SAH) constitutes the main modifiable risk factor, contributing to the development of ischemic, hemorrhagic, and lacunar strokes, as well as dementia. Given the scarcity of educational initiatives addressing neurological outcomes associated with SAH and stroke, a health education intervention—implemented as a waiting-room activity—was conducted at a Family Health Unit in the southwestern region of the state of Pará in mid-April 2025. The target population consisted of users of the Brazilian Unified Health System (SUS) receiving care within the scope of primary health care (PHC). The intervention, carried out by faculty and medical students, aimed to enhance public knowledge regarding the signs and symptoms of SAH, the importance of appropriate investigation, diagnosis, and adherence to treatment, as well as to promote healthier lifestyle habits, including the avoidance of smoking and alcohol consumption. The community demonstrated clear comprehension of the information provided, expressing interest and effectively assimilating the content related to SAH and stroke. This experience underscores the relevance of public policies that foster educational initiatives within PHC, as population-level knowledge is essential for the prevention of chronic non-communicable diseases.